Proposta e análise de técnicas de MPPT e LVRT aplicados em sistemas eólicos - Silva Neto, Miguel Eneas (2021)
This work proposes a new MPPT method called Hybrid P&O (P&O-H). For this, a study of the maximum power point tracking algorithms (Maximum Power Point Tracking - MPPT) and voltage sag mitigation is known in the literature as Low Voltage Ride Through (Low Voltage Ride Through - LVRT) applied in systems wind turbines connected to the electricity grid through the back-to-back converter associated with the permanent magnet synchronous generator (Permanent Magnet Synchronous Generator - PMSG). A literature review was carried out on the most diverse methods of MPPT mentioned in the literature, it is possible to identify an area still little studied in the methods of the perturb and observe type (Perturb & Observe - P&O), enabling the development of more efficient and robust power extraction techniques. The P&O-H has advantages over other algorithms because it does not require knowledge of the system parameters, as well as it does not need to measure the wind, making it perfectly adaptable to changes in the environment. Also, a study of the LVRT mitigation techniques was applied, being proposed in this work control of low cost and easy to implement, the LVRTH. The simulations were carried out to prove the efficiency of both the P&O-H, presenting contributions in the power extraction, as well as the LVRT-H, presenting contributions in the reduction of the average action of the controllers of the network-side converter (CLR) and contributing to the stability of the system against disturbances from the grid. Finally, future works are indicated.